Pendampingan Belajar Bahasa Inggris Melalui Kegiatan English Class Bagi Siswa MAN 2 Situbondo - Musdalifah Musdalifah; Nazilul Umami; Mega Selviana Dewi (LP2M Universitas Ibrahimy, 2023)
English is a language that must be master by learners. One of the important components in learning English is mastering vocabulary well. In addition, the right method is also needed to be able to develop an English skill, these are 4 skills that need to be developed, namely listening, reading, writing and speaking. In this case, the students of MAN 2 Situbondo learn together by